Peningkatan Kapasitas Kader Posyandu di Wilayah Kerja Puskesmas Perumnas Utara Kota Cirebon - Heni Fa'riatul Aeni; Herlinawati; Ulfatul Laeli Nadia; Diana Nurdianti; Sri Lestari; Nina Herlina (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
Training is a very important strategy for Cadres to increase their knowledge and skills so as to manage Integrated Healthcare Post (Posyandu) activities optimally. The main problem found among Posyandu cadres was the low level of proficiency and skills below standard. To strengthen cadre skills in Posyandu activities, it is necessary to perform Posyandu cadre training sessions through an increase in the capacity of Posyandu cadres. Activities were conducted through certain methods namely group discussion, brainstorming and demonstration regarding 25 basic skills of cadres in the health sector at Posyandu, as well as measuring and weighing practices. The results of the intervention showed an increase in cadres' knowledge level, with a mean pre-test score of 6.58 and a mean post-test score of 8.69. Furthermore, it was revealed that they were able to practice 25 basic cadre skills. An increase in the capacity of Posyandu cadres through discussion, brainstorming, demonstration along with the use of leaflet effectively could increase knowledge. Thus, it is expected to increase the frequency of training activities for Posyandu cadres in a sustainable manner by applying more varied methods.